Concept and Practices of Cyber Supply Chain in Manufacturing Context - Gani, Anisha Banu Dawood; Fernando, Yudi (IGI Global USA, 2018)
The objective of this chapter is to discuss the concept and practices of cyber supply chain (CSC) in manufacturing context. Technological advancements are drastically transforming manufacturing industry, which in turn drives the need for a digitally integrated supply chain. While CSC has its share of benefits, it is also vulnerable to cyber threats. In order to mitigate the risks, a comprehensive security measures must be undertaken in the areas of technology, organization, governance, and culture, and integrate them into the company's established risk management processes. To ensure a resilient CSC, all members of the supply chain network must play a role to protect their respective systems from potential breach.